2017
DOI: 10.1002/jctb.5468
|View full text |Cite
|
Sign up to set email alerts
|

A new source for developing multi‐functional products: biological and chemical perspectives on subcritical water extracts of Sambucus ebulus L.

Abstract: BACKGROUND To obtain bioactive fractions from plant material subcritical water is notably advantageous in comparison to any other technique. Excellent solvating properties and selectivity combined with finely tuned reactivity of subcritical water enable exploitation of the potential of plants. Herein subcritical water extraction was used for recovery of bioactive compounds from leaves, roots and fruits of Sambucus ebulus L. Extracts obtained were characterized in terms of biological and chemical fingerprints. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
1
8
1
Order By: Relevance
“…The results show moderate to strong correlations that are also significant for Hep‐2 and L cells (Table 2). Cvetanović et al 32 had proposed that these polyphenols exert anticancer activity through additive and synergistic mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…The results show moderate to strong correlations that are also significant for Hep‐2 and L cells (Table 2). Cvetanović et al 32 had proposed that these polyphenols exert anticancer activity through additive and synergistic mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study total phenolic content of dwarf elder's extract was 108.59 ± 3.11 mg GAE/ g DE. In previous studies, the estimated concentration of polyphenolic compounds varies from 43.47 mg GAE/g to 116.3 mg GAE/g extract (Meriç et al 2014;Topuzović et al 2016;Cvetanović et al 2017). Cvetanović et al (2017) reported 116.3 mg chlorogenic acid equivalent in subcritical aqueous extract of Sambucus ebulus leaves with Serbian origin.…”
Section: Determination Of Total Phenolic Content and Radical Scavenging Activitymentioning
confidence: 99%
“…In previous studies, the estimated concentration of polyphenolic compounds varies from 43.47 mg GAE/g to 116.3 mg GAE/g extract (Meriç et al 2014;Topuzović et al 2016;Cvetanović et al 2017). Cvetanović et al (2017) reported 116.3 mg chlorogenic acid equivalent in subcritical aqueous extract of Sambucus ebulus leaves with Serbian origin. Topuzović et al (2016) reported 43.47 mg GAE per gram aqueous extract of leaves obtained by 24 h infusions.…”
Section: Determination Of Total Phenolic Content and Radical Scavenging Activitymentioning
confidence: 99%
“…The knowledge of organic chemistry and growth in the pharmaceutical field have led toward the discovery of synthetic medicine but have also impacted the side effects and the high cost as a negative image of these discovered drugs. This ultimately has attracted the health-promoting effects of the natural products to be used as medicinal products ( Cvetanović et al, 2018 ). Many plants having culinary uses have been detailed scientifically against worldwide common diseases like diabetes mellitus (DM), Alzheimer's, and cancer, owing to their medicinal properties.…”
Section: Introductionmentioning
confidence: 99%